2016
DOI: 10.1007/s11064-016-2070-2
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Cerebral Cortical Glucose and Glutamine Metabolism Precedes Amyloid Plaques in the APPswe/PSEN1dE9 Mouse Model of Alzheimer’s Disease

Abstract: Alterations in brain energy metabolism have been suggested to be of fundamental importance for the development of Alzheimer's disease (AD). However, specific changes in brain energetics in the early stages of AD are poorly known. The aim of this study was to investigate cerebral energy metabolism in the APPswe/PSEN1dE9 mouse prior to amyloid plaque formation. Acutely isolated cerebral cortical and hippocampal slices of 3-month-old APPswe/PSEN1dE9 and wild-type control mice were incubated in media containing [U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 37 publications
1
47
0
Order By: Relevance
“…This implies that alterations in glutamine metabolism may be early transformations in the pathogenesis of Alzheimer's disease. 38 Since the accumulation of amyloid plaques has been associated with inflammation, oxidative stress and mitochondrial dysfunction, 39 perhaps exogenous glutamine can protect against this in the early phrases of the disease.…”
Section: Biological Plausibilitymentioning
confidence: 99%
“…This implies that alterations in glutamine metabolism may be early transformations in the pathogenesis of Alzheimer's disease. 38 Since the accumulation of amyloid plaques has been associated with inflammation, oxidative stress and mitochondrial dysfunction, 39 perhaps exogenous glutamine can protect against this in the early phrases of the disease.…”
Section: Biological Plausibilitymentioning
confidence: 99%
“…The reduced labeling observed from incubations with [U- 13 C]glutamine could arise from reduced neuronal TCA cycle activity, as recently shown in a mouse model of early AD [19]. If the TCA cycle activity is decreased, the need for introduction of α -ketoglutarate derived from glutamine through glutamate likewise falls, leading to reduced 13 C labeling.…”
Section: Discussionmentioning
confidence: 78%
“…Acutely isolated brain slices were prepared as previously described [19, 20]. Briefly, animals were euthanized by cervical dislocation and the brain excised into ice-cold artificial cerebrospinal fluid (ACSF) containing the following in mM: NaCl 128, NaHCO 3 25, KCl 3, CaCl 2 2, MgSO 4 1.2, and KH 2 PO 4 0.4, pH = 7.4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Anderson et al (2017) observed that reduced glutamine uptake and hampered oxidative glutamine metabolism precede amyloid plaque formation in APPswe/PSEN1dE9 mice compared to controls. This implies that alterations in glutamine metabolism may be early transformations in the pathogenesis of Alzheimer's disease [35]. Since the accumulation of amyloid plaques has been associated with inflammation, oxidative stress and mitochondrial dysfunction [36], perhaps exogenous glutamine can protect against this in the early phrases of the disease.…”
Section: Biological Plausibilitymentioning
confidence: 99%